STUDI PREVALENSI GAKY DI KABUPATEN BANYUMAS TAHUN 2007 - Erna Kusumawati; Dwi Sarwani Sri Rejeki; Misbakhul Munir (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2008)
Iodium Deficiensy Disorder (IDD) is a group of symptom which arising from body lacking of element iodium continually within sufficiently long, one of indicator used to measure the level of problem in community that is by measure of prevalensi endemic thyroid with Total Prevalency Goiter (TGR) The objectives of this study was to prevalensi IDD at women in reproductive age (WUS) in Banyumas regency year 2017. The type of this research was descriptive survey with cross sectional study. Sampel in this this research is WUS (15-49 year) amounting to 500 people coming from 5 district in Banyumas Regency. Data collecting conducted by observation with Urinary Excretion Iodine (UEI), inspection of degree of GAKY with palpalasi method. This survey is executed in August September 2017. Research result with palpalasi found the amount of Total Goiter Rate at WUS in Banyumas Regency Year in 2017 is 11,4% endemic category with detail degree of IA and IB (3,4%), II (4,0%). At inspection of UEI show has varying with value of lowers 3, highest value 296, average value 192,82 with standard of deviasi 64,40. At inspection of UEI known was 10,1% WUS of include in deficiencies category of iodium with heavy deficiencies (1,2%), moderate (2,8%) and lowers (6,2%). Require to continue to be improved by Communication Information and Education (KIE) so that knowledge of community concerning GAKY mount, so that effect at decrease of prevalensi GAKY.